An integrative review of the factors related to building age‐friendly rural communities. Issue 17 (24th April 2016) - Neville, Stephen; Napier, Sara; Adams, Jeffery; Wham, Carol; Jackson, Debra
Abstract : Aim and objectives: To identify the theories and concepts related to building age‐friendly rural communities. Background: Global population is rapidly ageing. Creating environments that support active ageing was a catalyst for the World Health Organization to develop Global Age‐Friendly Cities guidelines. Although the age‐friendly movement has captured the attention of some countries, little is known about the participation of older people in rural settings. Method: An integrative review approach was employed to summarise the research literature on this topic. Using a systematic search strategy, databases including Discover (EBSCO's electronic database system), Web of Science, Scopus, PubMed, CINAHL, PsycINFO, Medline and Google Scholar were searched. Primary, peer‐reviewed studies were included if published during 2007–2014 in the English language. Results: Nine studies were eligible for inclusion. The studies were set predominantly in Canada, with the exception of one from Ireland. The findings were summarised and clustered into main topics which included: theoretical perspectives; geographic and demographic characteristics; collaboration and partnerships; sustainability and capacity; and finally, future research agendas. Conclusions: Rural communities are changing rapidly and are becoming increasingly diverse environments. Community characteristics can help or hinder age‐friendliness. Importantly, the fundamental starting point for age‐friendly initiatives is establishing older peoples' perceptions of their own communities. Relevance to clinical practice: It is important for nurses, working in primary health care settings, to understand the needs of older people in the communities in which they practice. This includes the community characteristics that can be enablers and barriers to older people being able to remain and age within their own communities.